Histomorphometric and quantitative aspects of ovarian of Patagioenas maculosa (Aves, Columbidae) - Maron, Carina (2012)
Structural and quantitative variations of the ovary of Patagioenas maculosa were analyzed. Thirty five adult females were captured in Department Río Primero (Córdoba, Argentina), during the reproductive cycle from 2005 -2006. Gonads were removed, weighed and fixed in formalin buffered to pH 7.0 and processed according to the technique of embedding in paraffin. In the most bird, the ovary morphohistological analyses revealed a marked development of the gonad from May to February with 4 -5 yellow vitelogenic follicle ≥ 4 mm and preovulatory follicle. The gonadal weigth increased showing the highest value in September –October,agreed with the morphological characteristic of gonadal recrudescence phase. After oviposition the few developing follicles and posovulatory follicle and abundant atretic follicle indicated the onset of ovarian regresion. In the months of March and April the ovary showed the appearance of gonadal rest with abundant primary ocytes, previtellogenic and white vitelogenic follicle ≤ 2 mm, scarce yellow vitelogenic follicle ≥ and small atretic follicle The minimum gonadal weight was registres in March. The results of this study it appears that C. maculosa egg layed during the most part of the year and the prolonged gonadal activity of this birds would be related to the greater availability to food in the study area.